Sulina, Sulina / When There’s Water, There’s No Light. Narrative, Memory and Autobiography in a Romanian Town: Сулина, Сулина / Кога има вода, нема светлина. Нарација, сеќавања и автобиографија во романско гратче - Teampău, Petruţa; van Assche, Kristof; Kovačić, Marina (Identities: Journal for Politics, Gender and Culture, 2008)
Author(s): Petruţa Teampău and Kristof van Assche | Петрута Теампау и Кристов ван Аше Title (English): Sulina, Sulina / When There’s Water, There’s No Light. Narrative, Memory and Autobiography in a Romanian Town Title (Macedonian): Сулина, Сулина / Кога има вода, нема светлина. Нарација, сеќавања и автобиографија во романско гратче Translated by (English to Macedonian): Marina Kovačić | Марина Ковачиќ Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 33-70 Page Count: 37 Citation (English): Petruţa Teampău and Kristof van Assche, “Sulina, Sulina / When There’s Water, There’s No Light. Narrative, Memory and Autobiography in a Romanian Town,” Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009): 33-70. Citation (Macedonian): Петрута Теампау и Кристов ван Аше, „Сулина, Сулина / Кога има вода, нема светлина. Нарација, сеќавања и автобиографија во романско гратче“, превод од англиски Марина Ковачиќ, Идентитети: списание за политика, род и култура, т. 7, бр. 1-2 (лето 2008 - зима 2009): 33-70.